Fractured Care: A Window Into Emergency Transitions in Care for LTC Residents With Complex Health Needs. (March 2020) - Cummings, Greta G.; McLane, Patrick; Reid, R. Colin; Tate, Kaitlyn; Cooper, Sarah L.; Rowe, Brian H.; Estabrooks, Carole A.; Cummings, Garnet E.; Abel, Stephanie L.; Lee, Jacques S.; Robinson, Carole A.; Wagg, Adrian
Objective: For long-term care (LTC) residents, transfers to emergency departments (EDs) can be associated with poor health outcomes. We aimed to describe characteristics of residents transferred, factors related to decisions during transfer, care received in emergency medical services (EMS), ED settings, outcomes on return to LTC, and times of transfer segments along the transition.Method: We prospectively followed 637 transitions to an ED in British Columbia and Alberta, Canada, over a 12-month period. Data were captured through an electronic Transition Tracking Tool and interviews with health care professionals.Results: Common events triggering transfer were falls (26.8%), sudden change in condition (23.5%), and shortness of breath (19.8%). Discrepancies existed between reason for transfer, EMS reported chief complaint, and ED diagnosis. Many transfers resulted in resident return directly to LTC (42.7%).Discussion: Avoidable transfers may put residents at risk of receiving inappropriate care. Standardized communication strategies to highlight changes in resident condition are warranted.